To rewrite the polynomial \(x^2 + 4x + 4\) using the form \(x^2 + 2ax + a^2 = (x + a)(x + a)\), we need to identify \(a\).
In the expression \(x^2 + 4x + 4\):
- The coefficient of \(x\) is \(4\), which means \(2a = 4\). So, solving for \(a\), we have \(a = 2\).
- The constant term \(a^2\) should be \(4\) (since \(a = 2\), \(2^2 = 4\)).
Now, we can rewrite the polynomial as:
\[ x^2 + 4x + 4 = (x + 2)(x + 2) \]
Thus, the established polynomial is:
\[ x^2 + 4x + 4 = (x + 2)(x + 2) \]
So, the correct response is:
\(x^2 + 4x + 4 = (x + 2)(x + 2)\)